Public Policies on the Financing of Higher Education in Chile: 1970-2020; [Políticas Públicas Sobre Financiamiento de la Educación Superior en Chile: 1970-2020] - Caiceo-Escudero, J (FahrenHouse, 2023)
Until 1973 Higher Education in Chile was free for the 8 existing universities -2 publics and 6 privates-. The military dictatorship began to reduce the state’s contribution of funding through the implementation of a market policy in education; from 1981 on a larger decline begins and private universities are enabled to be created; to this end, it issues three decrees amending the composition of higher education. This situation was maintained with the return to democracy in 1990 and scholarships and financial support were established with a return. Starting in 2016, the gratuitousness’s policy began again, initially for 50% of students from lower-income families; it was then increased to 60% and will gradually increase in time by increasing the percentage to reach 100%. It is pursued, on the basis of the relevant legislation, to analyze the period under study with a historical-analytical methodology. © 2023 FahrenHouse. All rights reserved.